Right Posterior Segmental Hepatic Duct: Role of Intraoperative Cholangiogram to Prevent Extrahepatic Biliary Duct Injuries - Ikhwan, SM; Hairol, O; Razman, J; Zamri, Z; Affirul, C (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus